Expectations and prevalence of alcohol consumption in high school students - Hinojosa García, Laura; García García, Pedro; Jiménez Martínez, Aída Aleyda; Peralta Cerda, Elvia Guadalupe (Horizonte Sanitario, 2025)
Objective: identify the prevalence of alcohol consumption in high school students, know their expectations regarding consumption, as well as determine if there is a relationship between both variables.Materials and methods: quantitative, descriptive, correlational and cross-sectional study in a sample of 570 students, a personal data card and the Alcohol Consumption Expectations Questionnaire (AEQ) were used.Results: in relation to the sociodemographic characteristics of the participants, 50.2% were male, their age fluctuated between 17 and 19 years. 68.8% reported having consumed alcohol at some point in their lives, 27.2% of the participants considered that when consuming alcohol there would be changes in social behavior, the prevalence of global, classic, current and instantaneous alcohol consumption showed a positive and significant relationship. (p